Indeks Saham Syariah Indonesia: Pengaruh Faktor Makro Ekonomi Di Masa Pendemi Dan Pasca Pendemi - Hidayat, Achmad; Mubyarto, Novi; Ritonga, Ahmad Husein; Sunarti, Zeni (Jurnal Ilmiah Ekonomi Islam, 2023)
This research is presented based on an event where the Indonesian Stock Exchange (IDX) recorded an ISSI increase of 13.9% from March 2 2020 to March 31 2021 in line with an increase in the Islamic stock market index. This strengthening actually occurred at a time when Indonesia's macroeconomic conditions experienced a contraction during the Covid-19 pandemic. According to Martalena and Maya Melinda there are at least five economic factors that can influence stock price movements, namely inflation, government policies regarding fuel prices, national income per capita, currency exchange rates, interest rates. So based on this theory, researchers took three factors that influence stock price movements in the Indonesian Sharia Stock Index in 2020-2022, namely Interest Rates, Rupiah Exchange Rate and Inflation. This study uses a descriptive quantitative approach with multiple linear regression analysis.. The results of this study found that Interest Rates and Rupiah Exchange Rates had a significant negative effect on ISSI while Inflation had a significant positive effect. where if inflation strengthens, ISSI will also increase based on the period mentioned. The level of explanation of the independent variable on the dependent variable is 69.1% where 30.1% is influenced by other variables.